THE POTENTIAL ROLE OF FATTY ACIDS IN ATTENTION-DEFICIT / HYPERACTIVITY DISORDER (ADHD) (Elsevier, 2000)

(untitled)
As currently defined, attention-deficit hyperactivity disorder (ADHD) encompasses a broad constellation of behavioural and learning problems and its definition and diagnosis remain controversial. The aetiology of ADHD is acknowledged to be both complex and multifactorial. The proposal considered here is that at least some features of ADHD may reflect an underlying abnormality of fatty acid metabolism. Clinical and biochemical evidence is discussed which suggests that a functional deficiency of certain long-chain polyunsaturated fatty acids could contribute to many of the features associated with this condition. The implications in terms of fatty acid treatment proposals are also discussed; such a form of treatment is relatively safe compared to existing pharmacological interventions, although further studies are still needed in order to evaluate its potential efficacy in the management of ADHD symptoms.